Al-Doped CoP nanoarray: a durable water-splitting electrocatalyst with superhigh activity. Issue 14 (28th March 2017) - Zhang, Rong; Tang, Chun; Kong, Rongmei; Du, Gu; Asiri, Abdullah M.; Chen, Liang; Sun, Xuping
Abstract : An Al-doped CoP nanoarray on carbon cloth (Al-CoP/CC) is superior in activity to CoP/CC for electrochemical water splitting and its two-electrode electrolyser needs a voltage of 1.56 V for 10 mA cm −2 in 1.0 M KOH. Abstract : The scalable production of hydrogen fuel through electrochemical water reduction needs efficient Earth-abundant electrocatalysts to make the whole water-splitting process more energy efficient. In this Article, we report that an Al-doped CoP nanoarray on carbon cloth (Al-CoP/CC) behaves as a durable hydrogen evolution electrocatalyst with superhigh activity in 0.5 M H2 SO4 . It demands a pretty low overpotential of 23 mV to drive a geometrical catalytic current density of 10 mA cm −2, outperforming all reported non-precious metal catalysts. Density functional theory calculations reveal that Al-CoP has a more thermo-neutral hydrogen adsorption free energy than CoP. Notably, this Al-CoP/CC is also superior in activity and durability as a bifunctional catalyst for alkaline water electrolysis, and its two-electrode water electrolyser delivers 10 mA cm −2 water-splitting current at a cell voltage of 1.56 V in 1.0 M KOH. This work offers us an attractive cost-effective catalyst electrode in water-splitting devices for large-scale production of hydrogen fuels.